Trump’s Impeachment: The Greed for Presidential Power and the Limits of the Constitution - Abdelkrim Dekhakhena (Jurnal Studi Pemerintahan, 2020)
Prompted by populist rhetoric Donald Trump has spent his time in office trying to bend the conventions of the American presidency to his will. Since taking office, he has repeatedly taken unilateral actions to defy Congress and push the limits of his own power. Now he appears to be trying to override a core principle of democracy: that no one is above the law. Faced with an impeachment inquiry, Trump has openly defied the core constructs of the Constitution. President Donald Trump is incensed by the idea of co-equal branches of government and rejects the House’s right to investigate him. The main aim of this paper is to find out the extent of constitutional limits put on the Executive and the validity of the system of check and balance and to what extent executive privilege would save Trump. Thus, this paper reveals that regardless of the result of the impeachment process, it is critical that those on both sides of the political spectrum work to assure that the growth in presidential power is at least checked, if not reversed.